Thermo-catalytic reforming pyrolysis of ensiled Saccharina latissima dominated macroalgal pellets for bioenergy production - Marie E. Kirby; Trisha Toop; Miloud Ouadi; Lesley McEvoy; Christine Rolin; Rhiannon Inkster; Philip W. Dyer; Michael K. Theodorou (Energy Conversion and Management: X)
Marine macroalgae is a biomass resource for the manufacture of fuels and chemicals, which can be sustainably harvested from seaweed farms or from man-made structures where it accumulates as a biofouling organism. However, in temperate regions farmed macroalgae can only be harvested between late Spring and early Summer, limiting year-round availability. Here we show that a conventional grass ensilage procedure preserves Saccharina latissima dominated biomass on the tonne scale for 30 months, enabling year-round use of this biomass. Following processing, the resulting dried and pelletised ensiled macroalgae material was subject to Thermo-Catalytic Reforming™, comprising sequential pyrolysis (450 °C) and either dry or steam catalytic reforming (700 °C) processes. Both processing methods produced a mixture of bio-oil (1.6–1.9 wt%) and hydrogen-rich permanent gases (30.9–31.1 wt%) with higher heating values of 34.8–35.4 MJ/kg and 18.0–24.2 MJ/m3, respectively, together with char (45.5–48.5 % wt). The permanent gases can be used directly for heat generation, while hydro-treatment of the bio-oil would afford a material that can be blended with traditional transport fuels. This work demonstrates that if operated at scale, the combined harvesting, ensilaging and Thermo-Catalytic Reforming™ of preserved macroalgal biomass offers a year-round decentralised energy resource.